Comparison Of Carlson Trophic State Index In Jatibarang Reservoir Using Landsat 8 OLI and Sentinel-2A MSI - Pratomo, Risdianto Adi (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2023)
Jatibarang Reservoir is located in Semarang City and has fisheries potential so the condition of water quality is important to know. Water quality monitoring can be known by analyzing the trophic status. The purpose of this study was to determine the spatial description of water quality parameters including secchi disk transparency, total phosphorus and chlorophyll-a concentration and also the distribution of trophic status in Jatibarang Reservoir. The study used a descriptive analysis method using Landsat-8 OLI (Operational Land Imager) and Sentinel-2A MSI (Multi Spectral Index) satellite image data to determine trophic status and field data as accuracy test. Data collection was carried by 7 stations. Analysis of data accuracy using standard error method and trophic status using Carlson Index. The results obtained for each parameter in the Landsat-8 OLI image are brightness 0.30, total phosphorus 0.74 and chlorophyll-a 1.41 while the regression results for the Sentinel-2A MSI are brightness 0.29, total phosphorus 0, 17 and chlorophyll-a 0.60. Sentinel-2A MSI is better for estimating trophic status parameters than Landsat 8 OLI. The brightness field ranged from 0.22 to 0.32 meters, total phosphorus from 0.13 to 0.24 mgL-1 and chlorophyll-a ranged from 2.30 to 3.79 mgL-1. The value of Carlson's trophic status in Jatibarang Reservoir ranges from 58.76 to 63.21 which is included in the mild to moderate eutrophic fertility level.